An evaluation of comfort performance of prescribed uniform of selected security guards - Pelayo, Aisha Tabia; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The main objective of the study was to evaluate the comfort performance of the uniform of security guards as prescribed in Republic Act No. 5487. This research evaluated the comfort performance of the prescribed uniform in terms of physical and socio-psychological comfort aspects (Branson & Sweeney, 1991). The researcher adopted the descriptive method for research design, while purposive sampling method was used to identify and determine the number respondents. Out of 100 survey questionnaires distributed to the security guards of UP Diliman, 58 were returned and considered valid. Frequency distribution across variables such gender, age, schedule of work, agency and BMI were determined. The result of the study will be able to help the Supervisory Office for Security and Investigation Agencies (SOSIA) become aware if the security are comfortable wearing their prescribed uniforms. Security agencies, uniform suppliers and subcontractors may also use the obtained data as reference to create and to supply uniform by taking considerations the clothing comfort needs of the wearer. The study showed that the physical aspect is a more critical factor than the socio-psychological aspect. The physical aspects of comfort are more correlated with overall garment evaluation than psychological aspects of comfort (Sonatg, 1985-68). Fit ranks as the most important aspect of comfort, while ease of movement ranks second. Without garment impediment, they can perform their tasks efficiently and effectively. Overall, the respondents are satisfied with the thickness of the fabric, fitness of the uniform, texture of the uniform to the skin, and effect of line on their figure. Also, the uniform allows them for easy movement, gives them pride and sense of authority to deter criminal acts. They do not feel ill-at-ease while wearing it, and they say it is suitable to their role as security guards. They also say that their uniform color is appropriate to their job as security guard. Qualitative statements from the respondents indicate preference for a better design and material. The prescribed uniform as fashionable has neutral standing. The prescribed uniform is not considered fashionable as it is considered as more of a functional attire than aesthetic. Moreover, they seem to have neutral standing also on whether or not the uniform is giving enough warmth/coolness, and whether or not if their uniform is easy to maintain. The neutral stand by the respondents indicate that there could be changes that can be made to fabric for better comfort. The researcher reccomends the use of tropical fabric and fabric blends as per Sec 5 of Republic Act No. 9242. The use of herbal finishes to 100% polyester fabric may also be suggested.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Police, Private -- Uniforms; Police, Private -- Uniforms -- Social apects